Odpowiedzi

2009-12-03T16:30:48+01:00
4(x-2)-(x² +3x)= 4x-8 - x²-3x = x²+x-8
(x²-2x+1)(x+3)=(x+1)²(x+3)
(2x+1)³=2x³+6x²+6x+1
(√5-x)²=5-2√5x-x²
(3x-4)²- (x+3)(x-3)=3x²-24x+16 - x²-9 = x²-24x+7

jesli chodzi o wieksze rozpisanie, lub o rozwiazanie funkcji kwadratowej to napisz, to zedytuje
  • Użytkownik Zadane
2009-12-03T16:32:23+01:00
4(x-2)-(x² +3x)=4x-8-x²-3x=x-x²-8
(x²-2x+1)(x+3)=x³+3x²-2x²-6x+x+3=x³+x²-5x+3
(2x+1)³=(2x+1)(2x+1)(2x+1)= (4x²+2x+2x+1)(2x+1)= (4x²+4x+1)(2x+1) =8x³+4x²+8x²+4x+2x+1= 8x³+12x²+6x+1
(√5-x)²=(√5-x)(√5-x)=5-x√5-x√5+x²=5-2x√5+x²
(3x-4)²- (x+3)(x-3)= (3x-4)(3x-4)-x²-3x+3x-9 = 9x²-12x-12x+16-x²-9= 8x²-24x+7
1 5 1